Analysis of publications on Nursing Interventions Classification (NIC) from 1980 to 2004 (Revista Latino-Americana de Enfermagem, 2006)
This study aimed at reviewing the knowledge produced about the Nursing Interventions Classification (NIC) available in the scientific literature from January 1980 to January 2004. NIC is a taxonomy with activities performed by nurses. Authors searched Lilacs and Medline databases, materials at the Center for Nursing Classification-University of Iowa College of Nursing and a doctoral dissertation obtained from a private library. The works found referred to the application of NIC to practice, the languages used in information systems, the use of NIC in these systems and the presentation, construction, development and validation of a taxonomy, among others. Authors concluded that there are several possibilities related to the production of knowledge on NIC in Brazil and that it is necessary to encourage studies on this taxonomy, raising questions and generating new knowledge to contribute to the improvement of Brazilian Nursing.